System Analysis and Mathematical Model of Designing Remotely Operated Vehicle Support Vessels - Egorov, A.G.; Abdullayev, O.M.; Abdullayev, R.O. (Herald of Azerbaijan Engineering Academy, 2025)
A model for studying the scientifically based design of remotely operated vehicle support vessels (ROV support vessel) has been developed, taking the vessel as a functional system with a subsystem of installed hardware. The work proposes theoretical foundations for forming the main dimensions of the vessel. A structural and mathematical model has been formed that describes the formation of the main dimensions of the remotely operated vehicle support vessels (ROV support vessel). A structural and mathematical model for optimizing the main dimensions of the vessel is proposed, taking into account the optimization criteria. A structural and mathematical model has been developed that describes the formation of the surface of the ROV support vessel. Based on the developed structural and mathematical models for forming the main dimensions, the surface of the vessel, a structural and mathematical model has been proposed that describes the functional parameters of the ROV support vessel. As a result of theoretical research, directions for studying the design method described by the structural and mathematical model of the ROV support vessel, reflecting its functional qualities, have been proposed.